Skateboarding LA: Inside professional street skateboarding - Snyder, G. J. (New York Univeristy Press, 2017)
Skateboarding LA: Inside Professional Street Skateboarding Skateboarding LA is about professional street skateboarding, a highly refined, athletic and aesthetic pursuit, from which a large number of people profit. (Skateboarding has been estimated to be a $5 Billion dollar a year industry.) Street skateboarders see the world differently, because they are skating on it, and to do so they creatively interpret architectural features --ledges, banks, gaps, stairs and handrails—in order to perform tricks. The tricks they perform are filmed and photographed and then disseminated to a global subculture via numerous platforms--videos, magazines, social media, websites. Skaters do this to increase their reputations, and hence their earnings. This ethnographic study of skateboarding, based upon over 8 years of participant observation in Los Angeles offers thick cultural description that will provide outsiders some insight into the process of this complex, but mostly misunderstood subculture. The themes of this research revolve around the idea of subculture careers, subculture media, subculture enclaves and subculture community, all of which call for a re-assessment of much of the existing literature surrounding the sociological and political significance of subcultures. This detailed study of skating was facilitated by the author`s relationship to his key informant, former professional skater Aaron Snyder, who is also his younger brother. Together they show that more than petty vandalism and exaggerated claims of destruction, skateboarding creates opportunities for skaters the world over and draws highly talented people to cities where professional skateboarders congregate. Skateboarding LA is an ethnographic study of skateboarding, based upon over 8 years of participant observation in Los Angeles which offers thick cultural description that will provide outsiders some insight into the process of this complex, but mostly misunderstood subculture. Snyder shows that more than petty vandalism and exaggerated claims of destruction, skateboarding creates opportunities for skaters the world over and draws highly talented people to cities where professional skateboarders congregate.